Quattro matrimoni e una biblioteca Storia di una raccolta libraria e delle vite nascoste tra le sue pieghe - grifoni, giovanna (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2023)
This historical research starts from the books of Ambrósio Fernández Merino and explores the figure of their owner, a mysterious Spanish lawyer who lived in Florence. The result is the discovery of a little-known intellectual and of a woman who was, on the contrary, very well-known and present in the social chronicles of her time: Marie Louise La Farge. A wealthy American of French origins, divorced and married four times, she lived in London, Paris, Rome and died in Florence in 1899. After her will gave rise to a legal battle that reignited public interest on her life, she fell into oblivion. Her story resurfaced from some ownership notes found on several books of Merino's library, books owned by Louise's ex-husbands. The library was given to the University of Florence by the La Farge's heirs.